DEPFET active pixel detectors for a future linear e+e- collider - Alonso, Oscar; Fischer, Peter; Kreidl, Christian; Peric, Ivan; Knopf, Jan; Ritzert, Michael (IEEE transactions on nuclear science, 2013)
The DEPFET collaboration develops highly granular, ultra-transparent active pixel detectors for high-performance vertex reconstruction at future collider experiments. The characterization of detector prototypes has proven that the key principle, the integration of a first amplification stage in a detector-grade sensor material, can provide a comfortable signal to noise ratio of over 40 for a sensor thickness of 50-75 μm. ASICs have been designed and produced to operate a DEPFET pixel detector with the required read-out speed. A complete detector concept is being developed, including solutions for mechanical support, cooling, and services. In this paper, the status of the DEPFET R & D project is reviewed in the light of the requirements of the vertex detector at a future linear e+e- collider.
Im Titel sind "+" und "-" in e+e- hochgestellt
Gesehen am 12.05.2021